An economic model to assess the effectiveness of economic cooperation between Ukraine and international non-government organization - Durman, Olena; Durman, Mykola; Topalova, Elzara; Grytsak, Lyubomyr; Zhiliaieva, Oksana (Journal of Eastern European and Central Asian Research (JEECAR), 2021)
This study aimed to develop an econometric model for assessing the effectiveness of economic international cooperation between Ukraine and international non-governmental organizations. Based on the cognitive modeling method, the key indicators of the model influencing the socio-economic development of Ukraine were determined. With the cognitive map's help, the links' qualitative characteristics have been identified and argued between the socio-economic indicators of the country's development and the amount of funding attracted from foreign non-governmental organizations. The direction of influence between the indicators of socio-economic development and the volume of investment was determined using economic laws and expert assessments with the involvement of 35 professional experts. The scenario analysis made it possible to analyze the changes in the country's socio-economic development due to changes in the size and structure of investment funds receiving from international non-governmental organizations.